2007
DOI: 10.1089/thy.2007.0029
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Follicular Thyroid Carcinoma: Prognostic Factors and Relevance of Histological Classification

Abstract: PDFC has a more aggressive behavior than well-differentiated carcinomas; prognosis is related to indicators that are also relevant in patients with well-differentiated carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 41 publications
(53 reference statements)
3
42
1
3
Order By: Relevance
“…The expression of NIS, AIT, Tg, TPO, p138-DUOX, and p53 was evaluated by immunohistochemistry using specific monoclonal or polyclonal antibodies, as previously described (Lacroix et al 2004, Faggiano et al 2007, Pulcrano et al 2007). For GLUT-1 expression, a rabbit polyclonal antibody was used (A3536; dilution 1/200; incubation time: 60 min, Dako, Glostrup, Denmark).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The expression of NIS, AIT, Tg, TPO, p138-DUOX, and p53 was evaluated by immunohistochemistry using specific monoclonal or polyclonal antibodies, as previously described (Lacroix et al 2004, Faggiano et al 2007, Pulcrano et al 2007). For GLUT-1 expression, a rabbit polyclonal antibody was used (A3536; dilution 1/200; incubation time: 60 min, Dako, Glostrup, Denmark).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…CDK1 overexpression is also related to carcinoma differentiation (p < 0.0001), and is directly linked to cyclin A overexpression (p < 0.0001), but not to cyclin B1 overexpression (Ito et al, 2002). Cyclin B1 expression does not have any prognostic significance for poorly differentiated follicular thyroid carcinoma (Pulcrano et al, 2007).…”
Section: Thyroid Carcinomamentioning
confidence: 89%
“…Several studies have revealed overexpression of cyclin A and B1 in thyroid cancers, including follicular thyroid carcinoma (FTC), also its poorly differentiated form and thyroid lymphoma [18,19,20]. Mainly, cyclin A has been overexpressed in anaplastic thyroid carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%